2007
DOI: 10.1124/mol.107.041087
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor (PR) Isoforms PRA and PRB Differentially Regulate Expression of the Breast Cancer Resistance Protein in Human Placental Choriocarcinoma BeWo Cells

Abstract: Breast cancer resistance protein (BCRP) plays a significant role in drug disposition and in conferring multidrug resistance in cancer cells. Previous studies have shown that steroid hormones such as 17␤-estradiol and progesterone can affect BCRP expression in cancer cells. In this study, we investigated the molecular mechanism by which BCRP expression in human placental choriocarcinoma BeWo cells is regulated by progesterone. Transfection of the progesterone receptor (PR) isoforms PRA and PRB resulted in a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 37 publications
5
83
0
1
Order By: Relevance
“…The promoter of ABCG2 has been reported to contain an overlapping estrogen response element and a progesterone response element, which were shown to specifically bind ERα and progesterone receptor A and B (PRA and PRB), respectively. Expression of ABCG2 was reported to be induced by estrogen through ERα; however, enhanced expression of ABCG2 by progesterone was observed only in model cells expressing PRB, whereas PRA was shown to repress PRB activity (Ee et al, 2004;Wang et al, 2008).…”
Section: P0295mentioning
confidence: 97%
“…The promoter of ABCG2 has been reported to contain an overlapping estrogen response element and a progesterone response element, which were shown to specifically bind ERα and progesterone receptor A and B (PRA and PRB), respectively. Expression of ABCG2 was reported to be induced by estrogen through ERα; however, enhanced expression of ABCG2 by progesterone was observed only in model cells expressing PRB, whereas PRA was shown to repress PRB activity (Ee et al, 2004;Wang et al, 2008).…”
Section: P0295mentioning
confidence: 97%
“…Although the molecular mechanisms regulating the expression of ABCG2 remain unclear, many agents have been found to regulate the expression of ABCG2, such as human placental lactogen, human prolactin, and folate [42][43][44]. Yin et al found that transforming growth factor-beta decreased ABCG2 gene expression in SP cells from MCF-7 [27].…”
Section: Et Almentioning
confidence: 99%
“…Wang et al found there were progesterone response elements on the upstream of BCRP promoter [114] and they note that the identified PRE is exactly the same as the estrogen response element published by Ee et al [117]. They found that PRB is a strong activator of transcription of the BCRP promoter, and PRA represses the PRB activity in the human placental choriocarcinoma BeWo cells.…”
Section: Progesterone Receptor (Pr)mentioning
confidence: 63%
“…PR expression in breast cancer is also an important indicator of likely responsiveness to endocrine agents. It has been shown that PRA and PRB are expressed in similar amounts in most breast tumors [114]. Some data indicated that progesterone via PRs may be related to the regulation of MDR in breast cancer.…”
Section: Progesterone Receptor (Pr)mentioning
confidence: 99%